How Not to Build a Temple: Jacob, David, and the Unbuilt Ideal in Ancient Judaism - Mroczek, Eva (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2015)
Jacob and David share one distinction in early Jewish literature: both wish to build temples, but are denied by direct divine revelation—David in Chronicles, and Jacob in Jubilees. Considering these figures together through the motif of a denied sanctuary illuminates how early Jews conceptualized the temple, both earthly and heavenly. The prohibitions against building are also occasions for cultic inauguration, revelation of writing, and promises of an ideal or eschatological sanctuary. When the Jerusalem temple was considered less than ideal, a return to founding moments, when the temple was still unbuilt—but only a blueprint, vision, or promise—was an important theological move. In those primordial times, nothing had yet been constructed, so nothing could have been ruined; Jacob and David serve as exemplars of how to live when the ideal temple is not yet real. Considering them together provides a richer imaginative context for Chronicles, Jubilees, 11QT, 4QFlor, and other texts.